Speech Acts in the Selected and Award Winning Filipino Children Short Stories - Serenio, Frances Mae A.; Velasquez, Cindy A. (Indonesian Journal of EFL and Linguistics, 2019)
Children’s literature may be one of the most difficult genres to write, if not the most difficult. The writer has to take into consideration his or her aims in writing the story while focusing on other literary elements such as the theme and the plot at the same time. Not only that, he or she has to put in mind what kind of reaction he wants from his or her reader – whether it be amusement, rejection or wholesome acceptance through learning. The purpose of this study is to identify the different speech acts commonly found in contemporary children’s short stories particularly those which have been awarded as Palanca winners and those from the book entitled Filipino Stories for Filipino children (An Anthology from the UP Integrated School Creative Writing Classes) by Eleanor Eme Hermosa. The study is anchored on John Searle’s (1969) Speech Act Theory. In the analysis, it is found that children’s literature provides a didactic role. Consistent with this function, the speech act structure has observed didactic role found to be primarily informational, assertive, and expressive in nature. In the stories, some of the values that the writers aimed to teach the readers are nationalism, love and pride for parents and siblings, and appreciation for education.